Tick-Borne Viral Encephalitis Incidence in the Constituent Entities of the Russian Federation. Communication 2. Verification of Conformity of the Forecast Data and Seasonal Monitoring of Actual Morbidity Rates - A. Ya. Nikitin; E. I. Andaev; A. K. Noskov; N. D. Pakskina; E. V. Yatsmenko; E. V. Verigina; S. V. Balakhonov (Проблемы особо опасных инфекций, 2019)
Abstract. Despite the decreasing TBE incidence trend in Russia, the disease is considered an ongoing challenge for the state’s public health and economics. Objective of our study was to describe the algorithm of short-term incidence forecast of TBE, to evaluate the conformity of these data to factual incidence and the results of annual strategic seasonal monitoring which takes place across all the entities of Russia. In the paper, we described the procedure for providing short-term extrapolation of TBE incidence forecast onto the Russian territories, depending on the absence or presence of incidence change trends.Materials and methods. Utilized were the State statistics, “The data on infectious and parasitic diseases” (Form No 2), as well as the information on strategic monitoring for a period of 2007–2018. In order to determine the multi-year trend of epidemic process development, regression analysis was applied. If the trend was identified, predictions were made on its basis, if not – through calculating the long-term annual average. In all the cases, 95 % confidence interval for incidence trend deviation was considered. Comparative analysis of actual morbidity rates and predicted ones and the data on strategic monitoring was conducted by Student’s criterion.The commutations were performed using Excel software tools.Results and discussion. The study has demonstrated that the expected rates of TBE incidence are not statistically different from the actual incidence or the data from strategic monitoring. The underestimation of the epidemiological risk is found only in 4 out of 49 entities (8,2 %), and it is of note that in 3 of them it was less than 16 %. The data from operational monitoring are downward biased by reference to actual incidence, which is probably due to inclusion of TBE cases confirmed and/or manifested upon termination of incubation period after expiration of terms of weekly observations. The unified and simple approach that we proposed to TBE-incidence forecasting within the territory of Russia provides for correct information on expected epidemiological risk assessment and timely planning of required preventative measures.